2016
DOI: 10.1080/21505594.2016.1150401
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQA1/B1 alleles as putative susceptibility markers in congenital toxoplasmosis

Abstract: Host and parasite genotypes are among the factors associated with congenital toxoplasmosis pathogenesis. As HLA class II molecules play a key role in the immune system regulation, the aim of this study was to investigate whether HLA-DQA1/B1 alleles are associated with susceptibility or protection to congenital toxoplasmosis. One hundred and twenty-two fetuses with and 103 without toxoplasmosis were studied. The two study groups were comparable according to a number of socio-demographic and genetic variables. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In the case of Toxoplasma, studies of congenital infection have implicated a number of tolllike receptors and other immune response genes relating to increased risk. 74,75 In regards to infection in later life, a population study of 1227 individuals from a Mexican American community in Texas found that seropositivity to Toxoplasma was heritable with a heritability factor (H2) of 0.21 ± 0.05 (P < .001). However, specific polymorphisms significantly associated with Toxoplasma seropositivity were not identified.…”
Section: Interaction Of Toxoplasma With the Host Genomementioning
confidence: 99%
“…In the case of Toxoplasma, studies of congenital infection have implicated a number of tolllike receptors and other immune response genes relating to increased risk. 74,75 In regards to infection in later life, a population study of 1227 individuals from a Mexican American community in Texas found that seropositivity to Toxoplasma was heritable with a heritability factor (H2) of 0.21 ± 0.05 (P < .001). However, specific polymorphisms significantly associated with Toxoplasma seropositivity were not identified.…”
Section: Interaction Of Toxoplasma With the Host Genomementioning
confidence: 99%
“…The strength of this association matches several of our identified protective associations. In a congenital study examining 122 foetuses for toxoplasmosis where HLA class II molecules play a crucial role in immunity, HLA-DQA1*01:03 ( P -value = 0·0002 [Chi-square test], OR = 3·1) and HLA-DQA1*03:02 ( P -value = 0·0001 [Chi-square test], OR = 9·6) were found to be associated with increased susceptibility to congenital toxoplasmosis [40] . The magnitude of the HLA-DQA1*03:02 association is similar to our HLA-B*35:05 association with typical EPEC but is far stronger than any other HLA association identified.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in several countries of Southeast Africa, such as Zambia, South Africa, Eswatini (former Swaziland), Zimbabwe, Angola, Namibia, Tanzania, Madagascar, Uganda, Kenya, Ethiopia, and Mozambique, indicate prevalence of T. gondii infection that ranges from 4% to 93% in the general population [11][12][13]. Signs, symptoms, and the severity of T. gondii infection differs according to the immune status of the individual, the age in which the infection was acquired, and the genotype of the parasite involved [2,3,[14][15][16]. In immunosuppressed patients due to human immunodeficiency virus (HIV) or immunosuppressive therapy, toxoplasmosis is considered a life-threatening parasitic disease.…”
Section: Introductionmentioning
confidence: 99%